2000
DOI: 10.1038/sj.ijo.0801177
|View full text |Cite
|
Sign up to set email alerts
|

Association of Trp64Arg polymorphism of the β3-adrenergic receptor gene and no association of Gln223Arg polymorphism of the leptin receptor gene in Japanese schoolchildren with obesity

Abstract: OBJECTIVE: To investigate whether Trp64Arg polymorphism of the b b 3 -adrenergic receptor (b b 3 -AR) gene and Gln223Arg polymorphism of the leptin receptor (Ob-R) gene are associated with obesity in Japanese schoolchildren. DESIGN: Population study of participants from a rural town located within 50 km northeast of Tokyo based on school medical examinations. SUBJECTS: 553 Japanese schoolchildren (291 boys and 262 girls) who were 9 ± 15 y old with a mean age of 11.9 AE 1.8 y. MEASUREMENTS: DNA was extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 48 publications
7
62
3
1
Order By: Relevance
“…We found that a significantly higher percentage (37%) of middleaged Korean obese women had the Trp64Arg polymorphism when compared to non-obese women (19%). These results together with recent findings in Pima Indians (5), Mexicans (21), Japanese (22), Chinese (23), Finns (6), and Caucasians (7) suggest that this polymorphism for the ␤3-adrenergic receptor gene mutation may be involved in a genetic predisposition for obesity in Korean middle-aged women. However, some other previous studies have not supported an associa- Values are number (%).…”
Section: Discussionmentioning
confidence: 64%
“…We found that a significantly higher percentage (37%) of middleaged Korean obese women had the Trp64Arg polymorphism when compared to non-obese women (19%). These results together with recent findings in Pima Indians (5), Mexicans (21), Japanese (22), Chinese (23), Finns (6), and Caucasians (7) suggest that this polymorphism for the ␤3-adrenergic receptor gene mutation may be involved in a genetic predisposition for obesity in Korean middle-aged women. However, some other previous studies have not supported an associa- Values are number (%).…”
Section: Discussionmentioning
confidence: 64%
“…The higher BW was due to increased accumulation of BF, that is, children with Arg64 allele were more obese than the children without this allele. Endo et al (2000) also found that BMI of Japanese children with the Arg64Arg or Trp64Arg genotypes was significantly higher than in those with the Trp64Trp genotype, so the polymorphism of the 3-BAR gene is a genetic risk factor for obesity. In a recent Italian study (Strazullo et al, 2001), the role of Arg64 allele in the development of abdominal adiposity was suggested in adults.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have investigated the association of Trp64Arg polymorphism of the 3-BAR gene with obesity or weight gain, but the results are equivocal (Allison et al, 1998;Fujisawa et al, 1998). Some studies (Endo et al, 2000) showed that the frequency of this polymorphism in obese patients was significantly higher than in normal subjects and BMI was significantly higher in subjects with Arg64 allele than in those homozygous for the normal allele. Kadowaki et al reported higher BMI not only in homozygotes but also in heterozygotes compared to normal subjects (Kadowaki et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the beta-3 adrenergic receptor is predominantly expressed in visceral adipose tissue (Krief et al, 1993). Notably, the Arg allele of this SNP has been linked with increased BMI, adiposity and obesity in children (Arashiro et al, 2003;Endo et al, 2000;Erhardt et al, 2005;Ochoa et al, 2004;Park et al, 2005) supporting the evidence in adults Pierola et al, 2007), and the increased risk for obesity at this ADRB3 loci may be driven partly by an interaction effect of the PPARG SNP Pro12Ala Hsueh et al, 2001;Ochoa et al, 2004). Other studies in young children between the ages 4-10 years and in adolescents report no signifi cant effects of Trp64Arg variants on BMI, weight or height when this variant is examined in isolation (Cecil et al, 2007;Haworth et al, 2008a;Hinney et al, 1997;Kurokawa et al, 2003).…”
Section: Adrenergic Receptor Gene Variants -A Role In Polygenic Obesimentioning
confidence: 99%